Burkina Faso's Infrastructure : A Continental Perspective - Briceño-Garmendia, Cecilia; Domínguez-Torres, Carolina (World Bank, Washington, DC, 2017)
Infrastructure contributed 1.3 percentage points to Burkina Faso's annual per capita gross domestic product (GDP) growth over the past decade, much of it due to improvements in information and communication technology (ICT). Raising the country's infrastructure endowment to that of the region's middle-income countries (MICs) could boost annual growth by more than 3 percentage points per capita.Today, Burkina Faso's infrastructure indicators look relatively good when compared with other low-income countries (LICs) in Africa. Burkina Faso has made significant progress in developing its infrastructure in recent years. The rapid modernization of the ICT sector, around 60 percent of the population lives within range of a global system for mobile communications (GSM) cell-phone signal. The expansion of safe water and sanitation technologies in urban areas since the late 1990s and the establishment of a system for funding road maintenance (by reducing the cost of road travel) should pay long-term dividends to the economy. The Africa Infrastructure Country Diagnostic (AICD) has gathered and analyzed extensive data on infrastructure across almost all African countries, including Burkina Faso. The results have been presented in reports covering different areas of infrastructure including ICT, irrigation, power, transport and water and sanitation and various policy areas, including investment needs, fiscal costs, and sector performance.